Shear bond strength of orthodontic brackets bonded using halogen light and light-emitting diode at different debond times - Rebeca Di Nicoló; Maria Amelia Maximo de Araujo; Levy Anderson César Alves; Rodrigo Othavio de Assunção e Souza; Daniel Maranha da Rocha (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this in vitro study was to compare the photoactivation effects of QTH (Quartz-Tungsten-Halogen) and LED (Light-Emitting Diode) on the SBS (Shear Bond Strength) of orthodontic brackets at different debond times. Seventy-two bovine lower incisors were randomly divided into two groups according to the photoactivation system used (QTH or LED). The enamel surfaces were conditioned with Transbond self-etching primer, and APC (Adhesive Pre-Coated) brackets were used in all specimens. Group I was cured with QTH for 20 s and Group II with LED for 10 s. Both groups were subdivided according to the different experimental times after bonding (immediately, 24 h and 7 days). The specimens were tested for SBS and the enamel surfaces were analyzed according to the Adhesive Remnant Index (ARI). The statistical analysis included the Tukey's test to evaluate the main effects of photoactivation and debond time on SBS. The Chi-square test was used to compare the ARI values found for each group, and no statistically significant difference was observed. The debond time of 7 days for QTH photoactivation showed statistically greater values of SBS when compared to the immediate and 24 h periods. There was no statistically significant difference between the QTH and LED groups immediately and after the 24 h period. In conclusion, bonding orthodontic brackets with LED photoactivation for 10 s is suggested because it requires a reduced clinical chair time.